Depressive and anxiety symptoms among university students in Iceland - Andri Haukstein Oddsson 1984- (2017)
According to previous research, mental health problems among university students is a growing problem and there is evidence to suggest that depression and anxiety are one of the most prevalent health problems for student population (Lyubomirsky, Kasri, Zehm, 2003; National Center for Education Statistics, 2005). The purpose of this thesis was to evaluate the estimated prevalence of depressive- and anxiety symptoms among university students in Iceland, what variables differ on symptoms and their relation to quality of life. A web-based questionnaire was sent to students at Reykjavík University, University of Iceland and University of Akureyri. Participants were 2.737 and the mean age was 28 years (SD= 8.4). Depressive symptoms were measured with the PHQ-9 (Kroenke, Spitzer & Williams, 2001), anxiety symptoms were measured with GAD-7 (Spitzer, Kroenke, Williams, & Löwe, 2006) and to measure quality of life we used the Quality of Life Scale (Burckhardt & Anderson, 2003). The estimated prevalence of clinically relevant depressive symptoms was 34.4% and anxiety symptoms were 19.8% across the study sample. Results showed a difference between full-time and part-time students, indicating a higher mean score for depressive- and anxiety symptoms for full-time students. Students living with their parents proved to have a higher mean for depressive symptoms than students in other residence. No significant relationship was found between depressive or- anxiety symptoms and quality of life. In conclusion, high scores of depressive- and anxiety symptoms highlight the need to investigate what possible factors might influence students’ mental health. Keywords: estimated prevalence, depressive symptoms, anxiety symptoms.